Potencial nutricional e antioxidante do fruto do catolé (Syagrus cearensis) - Meireles, Bruno Raniere Lins de Albuquerque (2017)
Coco catolé (Syagrus cearensis) is a native palm of socioeconomic importance and nutritional for the population of the Brazilian seminarian, however more in-depth information about its potentialities are scarce. Thus, this work was carried out with the objective of generating information on this species native to the Paraiba caatinga, through the nutritional characterization and determination of the antioxidant potential of the pulp, almond and coconut oil, evaluating the phenolic extracts. The fruits were collected in the city of Lagoa Seca-PB and submitted to physical and physical-chemical characterization analyzes to evaluate their nutritional and antioxidant potential. The physical characterization of coco catolé showed its constitution in 51.36% of pulp, 44.23% of endocarp and 4.41% of almond. In the pulp, moisture (68.74%), ashes (1.91%), proteins (3.53%), lipids (0.46%) and carbohydrates (25.36%) allied to the pH of 5.1, showed the susceptibility of this fruit to the fungal action, being important to observe its storage conditions. In almond, with low moisture contents (6.51%), showed the protein content (9.95%) and lipid content (38.22%), confirming its oleaginous potential. For the pulp pigments, values of 6.38 and 1.86 mg / 100g of total flavonoids and carotenoids were found, respectively. The almond presented a representative profile of minerals: magnesium (143.02 mg / 100 g), potassium (515.35 mg / 100 g), manganese (2.44 mg / 100 g) and copper (1.76 mg / 100 g), the daily intake requirements according to current Brazilian legislation. The total phenolic content and antioxidant activity of coco catolé pulp and almond indicated considerable amounts of bioactive compounds with antioxidant potential. The physico-chemical characteristics of coconut oil are within the standards required by Brazilian legislation for unrefined and cold-pressed vegetable oils, with emphasis on the presence of tocopherols (1530 µg / g oil) and saturated fatty acids (84 %), with lauric acid (45.06%) being the major. The mixture of moderately polar solvents such as acetone-water was highly efficient for extracting the antioxidant compounds from the pulp and the almond. In the phenolic profile of the extracts evaluated, 2,5-dihydroxybenzoic acid, caffeic acid, p-coumaric acid, rutin, ellagic acid and vanillic acid were the natural antioxidants present in coco catolé (Syagrus cearensis). The study of the composition of the fruit contributed to the knowledge of the nutritional and functional properties of catolé, encouraging the economic aggregation of the species, fruit consumption and filling a gap still existing in the literature on the potential of this species.